2004
DOI: 10.1002/macp.200400137
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State Olefin Metathesis: ADMET of Rigid‐Rod Polymers and Ring‐Closing Metathesis

Abstract: Summary: Solid‐state olefin metathesis of rigid‐rod acyclic diene metathesis (ADMET) polymers and ring‐closing metathesis (RCM) have been investigated. 1,4‐Dipropoxy‐2,5‐divinylbenzene (4) was synthesized and used in a bulk ADMET polymerization to produce oligomers of dialkoxy poly(phenylene vinylene). The reaction was continued in the solid state, effectively doubling the molecular weight. Solid‐state RCM was investigated with a variety of solid dienes and metathesis catalysts, and demonstrated in low convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 47 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…Solid-state polymerization can be performed at low temperatures, avoiding side reactions. This benefit and the ability to obtain polymers with higher degrees of crystallinity constitute two of the primary advantages of solid-state polymerization. , …”
Section: Admet: the Future Revealedmentioning
confidence: 99%
“…Solid-state polymerization can be performed at low temperatures, avoiding side reactions. This benefit and the ability to obtain polymers with higher degrees of crystallinity constitute two of the primary advantages of solid-state polymerization. , …”
Section: Admet: the Future Revealedmentioning
confidence: 99%
“…Recently, it has been demonstrated that acyclic diene metathesis (ADMET) polymerization [7][8][9][10][11] offers a new possibility as the efficient route of π-conjugated materials [12][13][14][15][16][17][18][19][20][21][22][23][24]. We first demonstrated a synthesis of high molecular weight, all trans poly(9,9-di-n-octyl-fluorene-2,7-vinylene) (PFV) by ADMET polymerization of 2,7-divinyl-9,9-di-n-octyl-fluorene using Schrock type molybdenum-alkylidene [21].…”
Section: Methodsmentioning
confidence: 99%
“…Ru(CHPh)(Cl)2(IMesH2)(PCy3) (Cy = cyclohexyl, IMesH2 = 1,3-bis(2,4,6-trimethylphenyl)-2-imidazolidinylidene), was also effective for syntheses of high molecular weight poly(2,5-dialkylphenylene-1,4-vinylene)s (PPVs) [22], PFVs and poly(N-alkylcarbazole-2,7-vinylene)s (PCVs) [23] (Scheme 2). The fact introduced an interesting contrast, because the initial attempts by this approach afforded oligomer mixtures [12][13][14][15][16][17][18][19][20]. It turned out that an optimization of the reaction conditions (catalyst, monomer/catalyst molar ratios, initial monomer concentration, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas the use of ruthenium‐based catalysts for metathesis of olefins is known, such transformations are almost completely unexplored in the solid state . The first mechanochemical protocol for cross‐metathesis (CM) and ring‐closing metathesis (RCM) of solid and liquid olefins in the presence of the first‐ and second‐generation Grubbs and Hoveyda–Grubbs catalysts were reported in 2015 by Do et al, whereas Spekreijse et al reported mechanochemical immobilization of ruthenium catalysts in MOFs, enabling mechanochemical CM and RCM in >95 % yields.…”
Section: From Classical Organic Transformation To New Reactivitymentioning
confidence: 99%